Dental abnormalities in children with cleft lip with or without cleft palate - Agnieszka Lasota (Journal of Pre-Clinical and Clinical Research, 2021)
Introduction Cleft lip with or without cleft palate (CLP) is associated with hypodontia, supernumerary teeth, dysmorphology of the crown or root shape, teeth impaction and malposition. The prevalence of anomalies is higher than in general population.